Risk factors for obesity and overweight in Chinese children: a nationwide survey. Issue 9 (2nd August 2022) - Chen, JingNan; Jin, Lu; Wang, FengLei; Huang, Ke; Wu, Wei; Chen, RuiMin; Maimaiti, Mireguli; Chen, ShaoKe; Cao, BingYan; Zhu, Min; Wang, ChunLin; Su, Zhe; et al.
Abstract: Objective: This study aimed to analyze a comprehensive set of potential risk factors for obesity and overweight among Chinese children with a full range of ages and with wide geographical coverage. Methods: In the Prevalence and Risk Factors for Obesity and Diabetes in Youth (PRODY) study (2017‐2019), the authors analyzed 193, 997 children aged 3 to 18 years from 11 provinces, autonomous regions, and municipalities that are geographically representative of China. All participants underwent physical examinations, and their caregivers completed questionnaires including dietary, lifestyle, familial, and perinatal information of participants. A multilevel multinomial logistic regression model was used to evaluate the potential risk factors. Results: Among the actionable risk factors that were measured, higher consumption frequencies of animal offal (odds ratios [OR] for an additional time/day = 0.91, 95% CI: 0.88‐0.95, same unit for OR below unless specified otherwise), dairy products (0.91, 95% CI: 0.88‐0.94), freshwater products (0.94, 95% CI: 0.91‐0.96), staple foods (0.94, 95% CI: 0.92‐0.96), and coarse food grain (OR for every day vs. rarely = 0.92, 95% CI: 0.86‐0.98) were associated with lower relative risk of obesity. However, higher restaurant‐eating frequency (OR for >4 times/month vs. rarely = 1.21, 95% CI: 1.15‐1.29) and longer screen‐viewing duration (OR for >2 hours vs. <30 minutes = 1.16, 95% CI: 1.10‐1.22) were associated with higher relative risk of obesity. Increased exercise frequency was associated with the lowest relative risk of obesity (OR for every day vs. rarely = 0.72, 95% CI: 0.68‐0.77). Conclusions: Changes in lifestyle and diet of Chinese children may help relieve their obesity burden.